A comparative study of nurses’ competencies in integrating religion/spirituality into patient care - Jamileh Farokhzadian; Amirreza Sabzi; Zakieh Farmitani (BMC Health Services Research)
Abstract Background There is a need of research to evaluate and compare the competencies of nurses in integrating patients’ religion and spirituality into nursing practice in various settings, including general and psychiatric hospitals. By understanding the competencies of nurses working in different environments, tailored spiritual care training programs can be developed to meet their specific needs. This study aimed to evaluate and compare the competencies of nurses in integrating patients’ religion/spirituality into nursing practice in both a general and a psychiatric hospital. Methods This cross-sectional descriptive-analytical study was conducted in two hospitals affiliated with Kerman University of Medical Sciences in southeastern Iran. Quota sampling was used to select 200 nurses (100 nurses from each hospital) in 2023. The Religious/Spiritually Integrated Practice Assessment Scale (RSIPAS) was used to evaluate and compare nurses’ competencies in integrating the religion/spirituality of patients into their nursing practice. Results The study revealed that nurses’ competencies in integrating patients’ religion/spirituality into nursing practice were moderate in both general (122.39 ± 19.40) and psychiatric hospitals (110.82 ± 25.63). Nurses in the general hospital had significantly higher competency scores compared to those in the psychiatric hospital (t = 3.59, p = 0.001). The type of hospital, work experience, and the involvement of professionals in providing religion/spirituality care were significant predictors of nurses’ competencies in integrating patients’ religion/spirituality into clinical practice. Conclusions The moderate levels of competencies among nurses highlight the need for further education and training to effectively integrate patients’ religion/spirituality into nursing across various healthcare settings. The type of hospital also influenced their competencies. Therefore, it is crucial for nurses, particularly those working in psychiatric hospitals, to receive training that is tailored to the specific needs, culture, and context of their respective healthcare environments. It is essential to conduct a baseline assessment of nurses’ readiness and competencies before implementing appropriate training programs.